Forest Owners’ Perspectives Concerning Non‑Timber Forest Products, Everyman’s Rights, and Organic Certification of Forests in Eastern Finland - Muttilainen, Hanna; Hallikainen, Ville; Miina, Jari; Vornanen, Juha; Vanhanen, Henri (Small-scale Forestry, 2022)
Global trends towards the bioeconomy and multidimensional ecosystem-based approaches are transforming our understanding of forests and expanding access to forest management. The demand for non-timber forest products (NTFPs) is increasing due to the current trends in lifestyle and consumption. Forest owners play a key role in the supply of NTFPs. However, many forest owners are not committed to production or aware of the opportunities for production of their forests. Understanding better the family forest owners’ behaviour and decision making regarding NTFPs is needed to strengthen the role of NTFPs in the Finnish bioeconomy. In this study, forest owners’ perspectives concerning NTFPs, Everyman’s Rights, and organic certification of forests were identified. The survey data were collected by emailing the questionnaire to North Karelian forest owners and analysed by creating forest owner typologies based on their forest ownership motives and perspectives concerning NTFPs. Regarding forest ownership motives, four owner groups of relatively equal size were identified and named as recreationist, conservationists, timber producers, and resigning owners leaving the forest property to the next generation. Regarding their use of NTFPs and interest in producing NTFPs four groups of owners were identified: owners who 1) harvested NTFPs for household use or 2) sale, 3) would allow the harvesting of NTFPs not covered by everyman’s right, and 4) need more information on the joint production of timber and NTFPs not covered by Everyman’s Rights. Most owners were household users. The results can be utilised to promote NTFP production and advocate for the more effective organic certification of forests for different forest owner groups.